DISTRIBUSI FORAMINIFERA BENTONIK SEDIMENPALEO TSUNAMI LETUSAN GUNUNG KRAKATAU BERDASARKAN DATA INTI BOR U-6 DI DAERAH UJUNGKULON BANTEN - Fauzielly, Lili; Jurnaliah, Lia; Hamdani, A. Helman (Bulletin of Scientific Contribution, 2014)
The presence of microfossils in sediments on mainland can explain the phenomenon of paleo –tsunami. Foraminifera bentonik as indicators of depositional environment used in this study. The purpose of this study was to determine the distribution of depositional environments of sedimentary origin eruption of Mount Krakatau tsunami . According this study, tsunami sediments can be recognized begin depth 90 -120cm . From Mikropaleontologi quantitative analysis from 12 samples of sediment,was obtained of 2635 individual and 55 species of foraminifera bentonik . The dominant species is Streblus becarii Linnaeus , Planulina wuellerstorfi Schwager , Bulimina marginata d' Orbigny , Bolivina spathulata Williamson , Elphidium lessonii d' Orbigny , Euuvigerina peregrina Cushman. Depositional environment of origin of tsunami sediments is shelf –bathyal and inner –shelf lagoon.